Biotransformation of eugenol and isoeugenol to vanillin by Aspergillus Niger - Sasikala, Appalasuwami (2012)
Eugenol and isoeugenol are main chemical components of clove oil. These both chemical compounds are phenyipropene, the class of phenylpropanoids chemical compounds. Clove oil extracted from the leaves, stem, and buds of clove tree Syzygium aromaticum. It has clear to pale yellow oily liquid and used widely as an herbal drug. Eugenol and isoeugenol can produce vanillin by biosynthesis process. Vanillin is flavoring agent used extensively in food and perfume industry. Since consumer request on vanillin increasing, the study aim on producing vanillin compound by biosynthesis using Aspergillus niger. The objectives of the study are to learn the techniques of preparing the culture for growth of Aspergillus niger and to carry out biotransformation of eugenol and isoeugenol using Aspergillus niger. Methodology involves were culture growth of fungus, cultivation, inoculum development and analysis of compounds. The biotransformation process using Aspergillus niger is to change the eugenol and isoeugenol into vanillin compounds. All the compounds formed characterized by chromatographic technique using Gas chromatography-Flame Ionization Detector (GC-FID) and Thin Layer Chromatography (TLC).